Problems encountered with the capillary tube immunodiffusion method for detection of botulinal toxin. - Guilfoyle, D E (1980)
By using antitoxin specific for the neurotoxin molecule, the capillary tube immunodiffusion method did not detect low levels of crystalline toxin. Reactions described earlier with crude toxin and less specific antitoxin were probably due to nontoxigenic botulinal antigens.